2012
DOI: 10.1371/journal.pone.0046739
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Lenses and Prisms Lead to Postural Instability in Both Dyslexic and Non Dyslexic Adolescents

Abstract: There is controversy as to whether dyslexic children present systematic postural deficiency. Clinicians use a combination of ophthalmic prisms and proprioceptive soles to improve postural performances. This study examines the effects of convergent prisms and spherical lenses on posture. Fourteen dyslexics (13–17 years-old) and 11 non dyslexics (13–16 years-old) participated in the study. Quiet stance posturography was performed with the TechnoConcept device while subjects fixated a target at eye-level from a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In line with the above suggestion, and since the visual system has little tolerance to errors in convergence [ 29 ], a relevant question would be if incongruence affects not only instability [ 28 ], but also may increase muscular activity. In our study, the negative trial lenses put conflicting demands on the visual system during the Near-Far task.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In line with the above suggestion, and since the visual system has little tolerance to errors in convergence [ 29 ], a relevant question would be if incongruence affects not only instability [ 28 ], but also may increase muscular activity. In our study, the negative trial lenses put conflicting demands on the visual system during the Near-Far task.…”
Section: Discussionmentioning
confidence: 90%
“…One suggestion arising from those results was that oculomotor signals and gaze related activity in the neck muscles are involved in postural stability [ 27 ]. A more recent study from the same group investigated the effect of spherical and prisms lenses’ on postural stability [ 28 ]. They found that prism lenses induced the highest degree of body sway (destabilisation), but interestingly, they also found increased body sway with spherical minus lenses, and the body sway was most pronounced with the -1 D lens, compared with the -3 D lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncorrected or improperly corrected refractive errors have been identified as risk factors for visual, musculoskeletal and balance symptoms in people with normal vision who perform prolonged near activities during leisure or at work . Additionally, the use of optical magnification has been observed to affect neck and head posture, which may increase visual strain during continuous near work and result in neck or scapular area symptoms …”
mentioning
confidence: 99%
“…Several studies have showed that dyslexic children display different eye behavior (Kapoula & Bucci, 2007;Kapoula, Gaertner, & Matheron, 2012) while performing, for example, postural tasks. Employing the light touch paradigm to examine the use of sensory cues to postural control in dyslexic children (Viana et al, 2013) also allowed us to observe that dyslexic children, in using cues from the fingertip touching the bar, need to applied a slight higher amount of force than non-dyslexic children (Viana et al, 2013).…”
Section: Dyslexic Performance and Quality Of Sensory Informationmentioning
confidence: 99%